INVESTIGATION OF THE EFFECT OF TBLT-BASED DIGITAL STORYBOOK ON STUDENTS’ ENGLISH LEARNING IN SMP N 2 SINGARAJA - I Dewa Made Prema Nareswara; Ni Luh Putu Eka Sulistia Dewi; Anak Agung Gede Yudha Paramartha (Universitas Suryakancana, 2026)
The aim of this research was to investigate the considerable effects of utilizing a TBLT-based digital storybook on students’ English proficiency and four essential language skills. This study utilized a quasi-experimental design with a post-test control group. The population comprised 264 seventh-grade students from SMP N 2 Singaraja, with a sample of 63 students chosen through cluster random sampling from two classes deemed to be comparable. Data collection was conducted using three validated instruments: a lesson plan, a post-test, and an assessment rubric, all of which were confirmed for reliability by two experts. The study took place over five sessions, four of which were allocated to the treatment phase and one to post-testing. Following the post-test, data were analyzed using SPSS version 27. Both descriptive and inferential statistical analyses indicated significant differences in English proficiency and language skills between the Experimental and Control groups (Sig 0. 14), with the exception of reading, which exhibited a moderate effect.